Eugenics and the normal body: the role of visual images and intelligence testing in framing the treatment of people with disabilities in the early twentieth century. Issue 3 (4th May 2017) - Stephens, Elizabeth; Cryle, Peter
Abstract: This article examines how the emergence of a statistical concept of the normal at the end of the nineteenth century led to the development of a theory of eugenics, and examines the cultural pathways by which this theory came to shape both the public perception and institutional treatment of people now understood as disabled. The statistical idea of the normal and the theory of eugenics were developed simultaneously in the work of one man: Francis Galton, cousin of Charles Darwin and often identified as the first 'social Darwinist.' Beginning with an analysis of the role of composite photography in Galton's research, this article traces the historical co-emergence of normality and eugenics along two key lines of development: the use of new visual imagining techniques in the public sphere as a means by which to popularize these ideas amongst a general audience, and their application in the institutional and legal treatment of disabled people in the first three decades of the twentieth century. In so doing, the article intends to provide a careful history of the development and application of eugenical thinking and practice in the Anglophone world over this period of emergence and influence.